Evaluating the Role of Chatbot-Powered Applications in Enhancing Doctor-Patient Communication: Evidence from a Tertiary Healthcare Institution in Nigeria - Chinedu Okafor (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2011)
This study critically evaluates the role of chatbot-powered applications in enhancing doctor–patient communication at a tertiary healthcare institution in Nigeria. Specifically, it examines the level of awareness and usage, the effectiveness of chatbot mediated communication in improving clarity, responsiveness, and accessibility of medical information, as well as the challenges associated with its implementation. A sample of 283 respondents was determined using Taro Yamane’s formula from a population of 958, comprising both healthcare professionals and patients, with 270 valid responses analyzed. Data were collected through structured questionnaires and analyzed using descriptive statistics. The findings indicate a high level of awareness and moderate adoption of chatbot applications among respondents. The results further reveal that chatbot systems significantly improve communication efficiency by providing timely responses, simplifying medical instructions, and enhancing patient understanding. Additionally, the technology contributes to increased trust and engagement in healthcare interactions. However, several limitations were identified, including inadequate handling of complex medical inquiries, technical constraints, and concerns regarding data privacy and confidentiality. Despite these challenges, the overall impact of chatbot applications on healthcare communication is positive, suggesting their potential as complementary tools in clinical settings. The study recommends the integration of more advanced artificial intelligence features, continuous system optimization, enhanced data protection measures, and targeted training for both healthcare providers and patients. Policymakers are also encouraged to support the adoption of AI-driven communication systems to improve healthcare delivery outcomes. The study concludes that chatbot-powered applications can significantly transform doctor patient communication when effectively implemented and managed.